Does the early release of retirement savings prolong labor market participation for workers approaching retirement? Evidence from Australia's "Transition to Retirement Income Streams" program - Andrew Carter (IZA Journal of Labor Policy, 2022)
Australia's "Transition to Retirement Income Streams" (TRIS) program aims to prolong labor force participation for older workers (aged 55-65 years) by offering early access to a worker's compulsory retirement savings (superannuation). Using a difference-in-differences design, our results suggest a small labor supply response, which increases after the program's initial years. The size of the effects appears to be consistent with the program adoption profile, which was low initially. For this reason, our estimates should be viewed as a lower bound for the true effects. We find that individuals with higher incomes are more likely to adopt TRIS. At least half of the program participants appear to be using strategies to minimize tax, a behavioral response that seems at odds with the program's intent.
Keywords: J19; J26; H2; I38; 330; labor supply; impact evaluation; mature age workers; retirementsavings; transition to retirement